Significance of sulfogalactosylglycerolipid in male fertility: Studies using Cgt heterozygous mice - Kongmanas, Kessiri (University of Ottawa (Canada), 2008)
Sulfogalactosylglycerolipid (SGG) is a sulfoglycolipid present specifically at a substantial level in mammalian male germ cells. It has been shown to function as an adhesion molecule important for sperm-egg interaction and a structural lipid involved in formation of sperm lipid rafts during capacitation in vitro. Due to the unique characteristics and functions, SGG can potentially serve as a biomarker for sperm fertility as well as a target for development of a non-hormonal contraceptive. To confirm the in vivo roles of SGG, we sought for transgenic mice with reduced amounts of sperm SGG. Cgt knockout male mice, transgenetically deficient in UDP-galactose:ceramide galactosyltransferase (CGT), an enzyme involved in SGG synthesis, are infertile due to spermatogenesis disruption. However, the Cgt+/- males can still produce sperm and sire offspring. We hypothesized that Cgt+/- males, expected to have reduced SGG amounts, would have compromised fertilizing ability and could serve as in vivo models for studying roles of SGG in fertilization and spermatogenesis. Unexpectedly, our results revealed that Cgt+/- males exhibited unimpaired spermatogenesis and fecundity. Moreover, the levels of SGG as well as lipid profiles of sperm and testes of Cgt+/- mice were similar to those of the wild type, suggesting that compensatory mechanisms must have occurred to maintain SGG levels in the Cgt+/- mice. Although these results revealed that Cgt+/- mice could not be used as the animal models, they implicated significance of normal testis and sperm SGG levels in maintaining normal spermatogenesis and fertility. The possible compensatory mechanisms regulating SGG levels were further investigated in Cgt+/- mice. As expected, only half of Cgt mRNA expression level of the wild type was transcribed in the Cgt+/- testes; however, testicular CGT polypeptides as well as their enzymatic activities in the Cgt+/- mice were found at a comparable level to those of the wild type. On the other hand, no change was found in terms of mRNA levels, polypeptide levels or enzymatic activities of arylsulfatase A (ASA), the enzyme responsible for SGG degradation in the testis. In conclusion, the compensatory mechanisms for SGG level adjustment in Cgt +/- mice occurred through the biosynthetic pathway, rather than the degradation pathway, by increasing the CGT polypeptide expression level. Therefore, identification of specific spermatogenic cell stages, contributing to normal expression levels of CGT and SGG in the Cgt+/- testes warrants further studies, as these studies should provide useful information regarding CGT and SGG importance during male germ cell development. In addition, a new approach to produce the animal models that can produce sperm with reduced SGG levels should be attempted. The RNA interference (RNAi) techniques may be tried to achieve this goal.
Keywords: Biology, Animal Physiology.; Chemistry, Biochemistry.